2014
DOI: 10.1177/0040517514530033
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysiological comfort properties of different knitted fabrics used in cycling clothes

Abstract: In this paper, we measured the thermal and moisture management properties of six different types of polyester knitted fabrics that are used in the production of summer cycling clothes. The test samples were selected from the most commonly used fabric structures according to the results of a survey on a cycling team in Bursa. The fabrics were compared to determine which fabrics were more convenient for cyclists. Thus, we carried out objective fabric tests to determine the thermal resistance, water vapor resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…12 The thermo-physiological properties were defined as wear comfort in terms of thermal and moisture effects, 13 and they are estimated through thermal and water vapor resistance. 14 Generally, the wicking height indicates the liquid moisture absorption and transfer property; moisture management properties explain the liquid water absorption, spreading and one-way transfer properties; the drying performance is a common method to evaluate fast-dry fabrics; thermo-physiological comfort is assessed by thermal resistance and water vapor resistance; and cooling performance shows the overall thermal properties of dry and wet fabrics.…”
mentioning
confidence: 99%
“…12 The thermo-physiological properties were defined as wear comfort in terms of thermal and moisture effects, 13 and they are estimated through thermal and water vapor resistance. 14 Generally, the wicking height indicates the liquid moisture absorption and transfer property; moisture management properties explain the liquid water absorption, spreading and one-way transfer properties; the drying performance is a common method to evaluate fast-dry fabrics; thermo-physiological comfort is assessed by thermal resistance and water vapor resistance; and cooling performance shows the overall thermal properties of dry and wet fabrics.…”
mentioning
confidence: 99%
“…Like previous studies the relationship between the thermal resistance and the thickness (regression coefficient 0,69) and thermal resistance and density were observed (regression coefficient 0,76) between fabrics. 16 According to MMT test results of fabrics, the highest wetting time value was seen Type 11 -textured polyester mesh knitted fabric. The highest top absorption rate was seen in Type 10 moisture management type of polyester.…”
Section: Resultsmentioning
confidence: 97%
“…It was observed that the thermal resistance value of two ply textured polyester mesh knitted fabrics decreased with increasing density. Thus, if the fabric density increases, the thermal resistance will decrease [33]. Cubric et al (2013), reported that air entrapped in the knitted fabric structure plays a prevalent role in the thermal resistance of knitted fabrics [34].…”
Section: Thermal Resistancementioning
confidence: 99%